Performance of System of Wheat Intensification (SWI) and conventional wheat sowing under North Eastern Plain Zone of India - Kumar, Anil; Raj, Rishi; Dhar, Shiva; Pandey, U.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during the rabi seasons of 2011-12 and 2012-13 at Regional Station Indian Agricultural Research Institute, Pusa, Samastipur, Bihar. System of wheat intensification (SWI) with different plant geometry was compared with conventional line sowing method of wheat under sandy loam soil. Seed treatment comprises of treated and untreated seed were allocated in main plot whereas three plant geometry of SWI (10 × 10, 15 × 15 and 20 × 20 cm) and one conventional line sowing at 22.5 cm were allocated in sub-plot under split plot design with three replications. Treated seed gave relatively higher effective tillers, number of grains and 1000-grain weight of wheat as compared to untreated seed. SWI at 10 cm × 10 cm recorded significantly higher effective tillers (345.7 and 405.8 m–2) as compared to SWI at 15 cm × 15 cm or 20 cm × 20 cm spacing during both the years. SWI at 10 cm × 10 cm spacing recorded significantly higher grain yield (6.60 and 5.14 t ha–1) during 2011-12 and 2012-13, respectively over other treatments. Irrigation water productivity was highest in SWI method with 10 cm × 10 cm spacing (27.50 and 21.42 kg ha.mm–1) as compared to conventional line sowing (20.2 and 15. 8 kg ha.mm–1) in 2011-12 and 2012-13, respectively. Thus, there was water saving of 17.3 and 17.8% during 2011-12 and 2012-13, respectively in SWI method of wheat sowing as compared to conventional line sowing.